REZIM KEAMANAN MARITIM INDONESIA-FILIPINA DALAM PEMBERANTASAN PENYELUNDUPAN DI PERBATASAN LAUT SULAWESI - Loing, Micha Angelia; Oktavian, Riskey; Damayanti, Angel (Indonesian Journal of International Relations, 2025)
This article seeks to examine Indonesia and the Philippines in tackling various blue crimes on Sulawesi Sea borderline. It was reviewed using the theory of international regimes by Stephen D. Krashner and then elaborated with the theory of interdependence complexity, which was aligned along with the concept of blue crime. The research method used in this research is qualitative based on case studies, with data sources obtained from the results of the interview combined with documentation which is then validated with deductive analysis techniques. The results of the research found that maritime pathology in the Sulawesi Sea has experienced an increase in smuggling and produced various smuggling network motives, thus showing the limitations of maritime security actors in thoroughly investigating smuggling in border areas which resulted in the Sulawesi Sea becoming an arena for the complexity of interdependence between the two sovereign countries, reflecting a rift in the maritime security regime that has not been effective enough to be implemented